The legal status of widows and divorcees (janda) in colonial Bali. Issue 128 (2nd January 2016) - Creese, Helen
ABSTRACT: This article explores the legal status of widows and divorced women ( janda ) in Bali during the transition to Dutch colonial rule at the turn of the 20th century. It examines the Balinese law codes and their application in adat (traditional) courts to consider the ways in which widows and divorcees were able to claim recognition of their economic and social rights. At that time, the Dutch established the adat law system that provided separate civil laws and courts for each ethnic group in the Netherlands Indies. Balinese traditional law codes devote considerable attention to the regulation of female sexuality both within marriage and following separation or the death of a spouse, particularly in relation to rights to property and inheritance. However, they have little to say about the dissolution of marriage. Following the imposition of Dutch colonial rule, the pre-existing Balinese traditional law codes and legal norms continued to underpin the legal process administered through the colonial customary courts but were brought into alignment with modern legal practices. The colonial administration in Bali set out systematically to provide access to the legal process for women. A number of legal cases involving widows and divorcees based on adat law precedents were recorded in the Dutch compilations of adat law cases ( Adatrechtbundels ). These cases relate principally to disputes between widows and the families of their former partners and indicate that the legal status of Balinese widows and divorcees was formally recognised.